Sex-specific association between alcohol consumption and liver cirrhosis: An updated systematic review and meta-analysis - Llamosas-Falcón, Laura; Probst, Charlotte; Buckley, Charlotte; Jiang, Huan; Lasserre, Aurélie M.; Puka, Klajdi; Tran, Alexander; Rehm, Jürgen (Frontiers in Gastroenterology, 2022)
Different studies have shown that women develop liver diseases at lower levels of alcohol consumption than men. Our aim was to quantify the dose-response relationship between alcohol consumption and the risk of liver cirrhosis by sex and identify the differences between women and men. A systematic review was conducted using PubMed/Medline and Embase to identify longitudinal and case-control studies that analyzed the relationship between the level of alcohol use and liver cirrhosis (LC) incidence, and mortality (ICD-8 and ICD-9 codes 571 and ICD-10 codes K70, K73, K74). Pooled relative risks were calculated by random effects models. Restricted cubic splines were used to model the dose-response relationship. A total of 24 studies were included in the analysis. There were collectively 2,112,476 women and 924,853 men, and a total of 4,301 and 4,231 cases of LC for women and men, respectively. We identified a non-linear dose-response relationship. Women showed a higher risk for LC compared to men with the same amount of alcohol consumed daily. For instance, drinking 40 g/day showed RRs of 9.35 (95% CI 7.64-11.45) in women and 2.82 (95% CI 2.53-3.14) in men, while drinking 80 g/day presented RRs of 23.32 (95% CI 18.24-29.82) in women and 7.93 (95% CI 7.12-8.83) in men. Additional analyses showed that the higher risk for women was found for morbidity and for mortality. Understanding the influence of sex on the association of alcohol consumption and the risk of LC is needed to develop recommendations and clinical guidelines for prevention and treatment.